Homofobia, véu do real - Schirmer, Anderson (2016)
Very old phenomenon, persecution, aggression and death to homosexuals have been interpreted as problem of justice by the modern state and a contemporary issue for social scientists and political activists. The criminal acts reveal a series of negative thoughts associated with population of Lesbian, Gay, Bisexual, Transsexual and Transgender (LGBT), which produce a breakdown that provides them not only physical attacks, but also symbolic. These violent actions against these guys and the thoughts that lead to them are called homophobia. Our work examines homophobia from the point of view of Freudian-Lacanian psychoanalysis, not ignoring the contribution of other areas, especially the gender and sociology theories. After we approach the emergence of the term, we apply the effort of seeking to circumscribe the phenomenon of cross-disciplinary manner and investigate the gaps, knowledge and power, identifying their modi operandi, especially where it is most remarkable; we went to problematize it within the broad field and complex sexuality, as investigated and theorized by psychoanalysis, presenting and discussing in each plan that makes up this concept. Our progress, however, is proving harder to submit this issue to the scrutiny of what Lacan called the "field of jouissance" and, in particular, the contribution of his theory of sexualization. We start then crisscrossing the knot within the plane of the three dimensional record of the subject's structure, problematize it to discuss masculinity in the field of culture, in terms of identification, the sex partner of choice and above all jouissance positions. Homophobic speeches and sometimes data and details of crimes, will serve us as objects in discussion with our theory. Using the formula of the Lacanian sexuation, we ask: what is man to psychoanalysis? And what is a woman? Also interested in how we design and apply these categories in the understanding of otherness and the formulation of policy, whether or not exclusion. Still bring a discussion with queer theory, highlighting what it has in common with psychoanalysis, the subversive capacity and treatment to new desires settings, but also the differences between them. Our job propose to thinking the homosexualities and these aversions, said: homophobia. Our thesis will seek to bring this debate mainly in the real Lacanian field, with its ethical and political